1991
DOI: 10.1038/clpt.1991.55
|View full text |Cite
|
Sign up to set email alerts
|

Rebound insomnia after only brief and intermittent use of rapidly eliminated benzodiazepines

Abstract: In three parallel groups, brief and intermittent administration and withdrawal of triazolam, 0.5 mg, temazepam, 30 mg, and placebo were assessed in a 12-night sleep laboratory study of 18 subjects with insomnia. With this intermittent schedule both drugs improved sleep, with about one-third reduction in total wake time; this reduction was significant for temazepam but not for triazolam. Even though the periods of drug administration were quite brief, withdrawal of triazolam consistently produced rebound insomn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…This lack of significant side effects is consistent with our findings from our three previous sleep laboratory studies with temazepam [15][16][17][18] as well as studies by other investigators [19,20].…”
Section: Discussionsupporting
confidence: 83%
“…This lack of significant side effects is consistent with our findings from our three previous sleep laboratory studies with temazepam [15][16][17][18] as well as studies by other investigators [19,20].…”
Section: Discussionsupporting
confidence: 83%
“…One study [96] showed that triazolam is associated with rebound in somnia even after a single night's dose. In another study [97], triazolam and, to a much lesser degree, temazepam produced rebound insomnia after only 1 or 2 nights of adminis tration. This side effect makes intermittent use, which is the most preferred form of treat ment for insomniacs, of rapidly eliminated hypnotics problematic, as it predisposes to drug-taking behavior and increases the poten tial for drug dependence [97], 210 Vgontzas/Kales/Bixlcr M echanism s o f Benzodiazepine Side Effects…”
Section: Withdrawal Phenomena (Rebound Insomnia and Anxiety)mentioning
confidence: 99%
“…It is of interest that the group that had the most alcohol withdrawal rebound in the present study (lorazepam-treated multiple detoxification patients) also had the most drinking during this period. Rebound symptoms with benzodiazepines have been reported in other conditions, such as the short-term treatment of insomnia 43 and anxiety disorders. 44 It could be argued that the use of a longer-acting benzodiazepine for alcohol withdrawal might well prevent the problem of rebound symptoms.…”
Section: Discussionmentioning
confidence: 99%